Factors influencing the quality of life in survivors of differentiated thyroid cancer based on patient-reported outcomes: a single-center cross-sectional study - Dong, Zhizhong; Zhan, Xiangxiang; Liu, Wen; Rao, Dewei; Yang, Miao; Peng, Ying; Su, Yanjun; Cheng, Ruochuan (Frontiers in Endocrinology, 2025)
PurposeWhile the prognosis for differentiated thyroid cancer (DTC) is favorable, the health-related quality of life (QOL) of survivors is not well understood. This study aims to investigate the factors influencing the QOL of DTC survivors.MethodsA total of 860 DTC survivors who underwent thyroidectomy were surveyed. Participants completed the Chinese version of the Thyroid Cancer-Specific Quality of Life (THYCA-QOL) questionnaire, the European Organization for Research and Treatment of Cancer Quality of Life Core Questionnaire-C30 (EORTC QLQ-C30), and additional related questions. Multivariate regression analyses identified factors affecting survivors’ QOL.ResultsAmong the survivors, 65 patients (7.6%) reported long-term postoperative complaints, including fatigue, throat discomfort, neck/shoulder stiffness, weight gain, and insomnia, among others. The average THYCA-QOL summary score was 20.29, with the highest scores in problems with scar, psychological problems, gained weight, less interest in sex, and sympathetic problems. The average EORTC QLQ-C30 summary score was 82.59, with lower scores for emotional and cognitive on the functional scales, and higher scores for fatigue and insomnia on the symptom scales. Women, BMI ≥ 28, higher T-stage (T3 + 4), permanent hypoparathyroidism, recurrence reoperation, and more postoperative complaints were associated with poorer thyroid cancer-specific QOL, while age over 45 years was associated with better QOL. Longer postoperative follow-up (>6 months) and drinking were correlated with higher QLQ-C30 summary scores, while recurrence reoperation and postoperative complaints were associated with worse QOL.ConclusionsThe QOL of DTC survivors is influenced by multiple factors, with some patients experiencing long-term complaints. Attention to the QOL and postoperative complaints in DTC survivors is essential.